Sharing Real-Time Traffic Information With Travelers Using Twitter: An Analysis of Effectiveness and Information Content - Rahman, Rezaur; Roy, Kamol C.; Abdel-Aty, Mohamed; Hasan, Samiul (Frontiers in Built Environment, 2019)
Ubiquitous smartphone technologies and virtual social networks offer us a unique opportunity to instantly share information to a large number of people. Online social media platforms facilitate easy and rapid communication of real-time information by producing a huge amount of digital content. In this paper, we present an analysis of the data collected from 14 Florida Department of Transportation (FDOT) Twitter accounts created for sharing real-time traffic information. We analyze the activities, influence, attention received, and the effectiveness of gaining attention by these accounts. We propose several metrics in disseminating real-time traffic information. Using topic models, we also analyze the content of the shared information given in the tweets. Finally, we estimate an ordered logit model to determine the information value of a shared content based on its chance of getting retweeted. Based on the study, we propose a framework called Social Media-based Adaptive Real-time Traffic feed (SMART-Feed) that will significantly improve the effectiveness of real-time traffic information sharing through social media. Moreover, it will help assessing the value of real-time traffic information to travelers and developing social media strategies for sharing information.